2021
DOI: 10.1002/jctb.6747
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated lignocellulosic biomass digestibility in anaerobic digestion for biomethane production: microbial communities' structure and interactions

Abstract: Lignocellulosic biomass is a highly available and suitable candidate for biogas/biomethane production. However, high concentration of recalcitrant lignin is the major obstacle in successful anaerobic digestion (AD). The main aim of this review is to highlight the applications and challenges of lignocellulosic biomass in AD from the recent reports. Potential approaches to improve instabilities in mesophilic AD process (such as microbial communities' development, co-digestion, biofilm carrier's addition, and ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 206 publications
(227 reference statements)
0
3
0
Order By: Relevance
“…The presence of lignin in tomato plant remains interferes with the decomposition of organic matter and decreases the overall production of methane during anaerobic digestion [27]. Prior research has demonstrated that materials possessing a substantial amount of lignin exhibit a reduced ability to be broken down by biological processes and generate methane [27,32,64]. Hence, it is crucial to reduce the presence of tomato plants during the co-digestion of tomato wastes to maximise methane production or apply pre-treatment methods that will enhance tomato plants' degradability.…”
Section: Biogas Composition Of Various Substratesmentioning
confidence: 99%
“…The presence of lignin in tomato plant remains interferes with the decomposition of organic matter and decreases the overall production of methane during anaerobic digestion [27]. Prior research has demonstrated that materials possessing a substantial amount of lignin exhibit a reduced ability to be broken down by biological processes and generate methane [27,32,64]. Hence, it is crucial to reduce the presence of tomato plants during the co-digestion of tomato wastes to maximise methane production or apply pre-treatment methods that will enhance tomato plants' degradability.…”
Section: Biogas Composition Of Various Substratesmentioning
confidence: 99%
“…51 Agricultural residues contain lignocellulose and need pretreatment prior to AD because of their recalcitrant nature. 52 Pretreatment of lignocellulosic biomass with thermophilic microbial consortium (MC1) has been reported to enhance biogas and methane production yields. 53 Researchers have reported enhanced methane yield during AD using mesophilic (37 °C) microaerobic pretreatment by the aerobic bacterium Bacillus subtilis.…”
Section: Biochemical Conversionmentioning
confidence: 99%
“…AD is one of the most popular ways of handling OFMSW because contamination risks are minimized and biogas, a renewable energy source, is produced in a controlled process that benefits the environment. More than 20,000 biogas plants have been built worldwide [8,9]. On the other hand, it is worth adding that digestate sludge from an agricultural biogas plant can also be reused to produce biodegradable materials.…”
Section: Introductionmentioning
confidence: 99%